Sugar cane crop management by N‐fertilizer application affects the aromaticity of humic acid structures in the superficial layer in soil. (16th October 2018) - Assunção, S. A.; dos Anjos, L. H. C.; Pereira, M. G.; Lima, E.; Paz González, A.; de Oliveira, A. P. P.; García, A. C.
Abstract: The nitrogen (N) applied to soil in a sugar cane field is prone to loss because of leaching, volatilization and/or mineralization. The interaction of the applied N‐fertilizers and the organic matter present in the most superficial layer of the soils has not been studied much. In this study, we evaluated the effects of application of N‐fertilizer ((NH4 )2 SO4 ) on the structural characteristics of the humic acids present in the surface layer of soil in a sugar cane field. The results show that the application of 100 and 120 kg/ha (NH4 )2 SO4 contributed to the formation of more aromatic humic acids. It also favoured the transformation of more labile structures, such as carbohydrates (CAlk‐ di ‐O), and preserved the chemically more stable and recalcitrant structures CArom‐(H, R) and CArom‐(O, N). Our results would help in the proper management of the application of N‐fertilizers for optimum yield.